The Effect of Transportation Energy Consumption on the Wind Energy Efficiency and CO2 Emission in Taiwan - Liao, C.-H.; Ou, H.-H.; Yu, Y.-H.
Wind power has had a striking development in recent years. However, advanced materials and technology for manufacturing wind turbines are necessary but usually unavailable in a developing country like Taiwan. In such a case, the consumption of transportation energy, especially an international one, cannot be ignored while the energy efficiency of wind power systems is surveyed. Based on our analysis, three demonstration wind systems in Taiwan, Mailiao, Jhongtun, and Chunfong, were analyzed to examine how the consumption of transportation energy affects the energy return on investment (EROI)and CO2 emission for wind energy. We have found the EROI loss increases while the transportation energy consumption is considered. Notably, the transportation of mega wind turbines leads to more CO2 emission. Moreover, wind turbines in small load capacities have less transportation energy ratio, while mega turbines consume disproportionately more transportation energy.
Keywords: CO2 EMISSION; ENERGY EFFICIENCY; ENERGY RETURN ON INVESTMENT (EROI); INTERNATIONAL TRANSPORTATION; WIND ENERGY